MR/CT atlas of anatomy [ a comprehensive digital sectional imaging library - Küper, Klaus (Georg Thieme Verlag, 2001)
Shows digital sectional imaging anatomy in more than 3,000 MRI and CT scans, with over 150,000 individually labeled anatomic structures. Provides the anatomic information needed to acquire confidence in the evaluation of sectional anatomy